Das Lacan'sche Tier: Eine psychoanalytische Perspektive auf den Anthropozentrismus und die Ambivalenzen in der Mensch-Tier-Beziehung - Aigner, Andreas (Interdisziplinäre Tierethik | Interdisciplinary Animal Ethics, 2022)
Anthropocentrism and the fact that some animals are just considered a means to an end while others are loved are often subject to criticism in animal ethics. Drawing on the psychoanalytic theories of Jacques Lacan, the author examines how the apparent ambivalence in human-animal relationships is based on different forms of enjoyment. Referring to the Real, the Symbolic and the Imaginary, which according to Lacan define human reality, the author shows how enjoyment and its limits shape, for example, how we think about pets, farm animals or wild animals. This alternative perspective will contribute to a better understanding of the challenges in human-animal relationships